Lifestyle Intervention in Chronic Ischaemic Heart Disease and Type 2 Diabetes (the LeIKD study): study protocol of a prospective, multicentre, randomised, controlled trial. Issue 2 (8th February 2021) - von Korn, Pia; Sydow, Hanna; Neubauer, Sarah; Duvinage, André; Mocek, Anja; Dinges, Sophia; Hackenberg, Bjoern; Weichenberger, Mario; Schoenfeld, Julia; Amelung, Volker; Mueller, Stephan; Halle, Martin
Abstract : Introduction: Guidelines recommend lifestyle intervention in chronic ischaemic heart disease (CIHD) and type 2 diabetes mellitus (T2DM). However, evidence from randomised controlled trials is scarce in patients with combined entities. Methods and analysis: The Lifestyle Intervention in Chronic Ischaemic Heart Disease and Type 2 Diabetes (LeIKD) trial is a prospective, multicentre study that will randomise (1:1) patients with CIHD (ICD-10: I20-I25) and T2DM (ICD-10: E11) from one health insurance company into a lifestyle intervention (LS) or usual care (UC). Active LS consists of an individual combined exercise programme of strength and endurance training and nutritional counselling with regular feedback for 6 months. Intervention is supported by telemedicine. Follow-up without individualised feedback will continue for 6 months. The study aims to investigate whether an individualised telemedical supported LS intervention is superior to UC in improving cardiovascular risk factors, physical activity, quality of life, health literacy, major cardiovascular events and health economics in patients with both CIHD and T2DM. Primary endpoint is the change in HbA1c from baseline to 6 months. Ethics and dissemination: The study has been approved by the ethics committee of the Technical University of Munich (registration number: 144/18-S) and at each study site. The study will be conducted according to the World Medical Association Declaration of Helsinki, and results will be published in articles and reports. It is funded by the Federal Joint Committee (www.innovationsfonds.g-ba.de ), reference number 01NVF17015, which has no impact on data collection, analysis or interpretation. Dissemination is independent of the funding source. Trial registration number: Clinical trials.gov identifier: NCT03835923 . German registry for clinical studies (DRKS): DRKS00015140.